Takaful surplus management and allocation for various sustainable modes: Shari`Ah and regulatory requirements / Md. Habibur Rahman ... [et al.] - Rahman, Md. Habibur; Abdullah, Md. Faruk; Ab Ghani, Hartini; Lambak, Salman (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
The surplus refers to the balance remaining in the takaful fund after paying all claims and other obligations. This study aimed to explore surplus management and allocation in various sustainable scopes and discuss relevant Shari`ah and regulatory requirements. Data was collected primarily through qualitative interviews with market leaders comprising Shari`ah and operational experts in takaful. A thematic analysis was carried out to explore qualitative data. The study found that sharing with participants and operators, managing deficits of takaful funds, supporting takaful funds of other operators, financial assistance to micro-takaful, donating in waqf and other charity works, etc., are some notable scopes for surplus allocation. It identified some critical Shari`ah and regulatory requirements for surplus utilization, including consent of the participants, fairness and effective communication with them, viability and solvency of takaful funds, and overseeing surplus sharing practices. The study concluded that utilizing surplus in various sustainable modes promotes equitable wealth distribution, financial inclusion, and social well-being and helps to realize Maqasid al-Shari`ah. It posits a regulatory update to facilitate surplus allocation for various charitable scopes as the current regulation restricts it between participants and operators.